68Ga-PSMA-11 PET Represents the Tumoricidal Effect of 223Ra in a Patient With Castrate-Resistant Metastatic Prostate Cancer. (September 2016) - Ahmadzadehfar, Hojjat; Schlenkhoff, Carl Diedrich; Rogenhofer, Sebastian; Yordanova, Anna; Essler, Markus
Abstract : Abstract: A 64-year-old man with prostate cancer and an increasing prostate-specific antigen (PSA) level under therapy with abiraterone acetate underwent a therapy with 223 Ra. Before the first therapy and 4 weeks after the last cycle, the patient underwent 68 Ga-PSMA PET, which showed a clear response of bone metastases.